English language as a global language in the band Now United - Rocha, Vitória Caroline Souza da; Juchniewski, Dainara Taís (Notas de Pesquisa, 2024)
This teaching unit was developed with the aim of expanding the knowledge of students at a state school about English as a global language, and how this topic is present in the daily lives of these young people: social networks. The texts selected for the activities address the linguistic and cultural diversity of the musical group Now United, made up of members of different nationalities who communicate through the English language. The aim of creating and implementing this unit is to give students the opportunity to think about the social practices incorporated in the texts, as well as their lexicogrammatical structure and the way they relate to society, because when we educate students to be critical of the text they read, we help to form citizens capable of interacting more with the community, as well as defending their interests through language.